Adenosine Triphosphate Pool During the Growth Cycle in Streptococcus faecalis - Forrest, W. W. (1965)
Forrest, W. W. (University of Adelaide, Adelaide, South Australia). Adenosine triphosphate pool during the growth cycle in Streptococcus faecalis. J. Bacteriol. 90:1013–1018. 1965.—The adenosine triphosphate (ATP) pool has been studied throughout the growth cycle of Streptococcus faecalis. Normally, the pool is quantitatively related to the concentration of organisms and the growth rate, but deviations from these relationships can occur without affecting the growth rate of the organisms. A critical concentration of ATP seems necessary for exponential growth, and, at lower levels, only linear growth can occur. If no growth can take place, catabolism of added energy source gives rise to a large increase in the pool level. The pool level represents the balance between the demands of the organisms for energy and the supply of energy derived from catabolism of the substrate.